Time Restricted Feeding to the Light Cycle Dissociates Canonical Circadian Clocks and Physiological Rhythms in Heart Rate - Schroder, Elizabeth A.; Delisle, Brian P. (Frontiers in Pharmacology, 2022)
Circadian rhythms are approximate 24-hour biological cycles that optimize molecular and physiological functions to predictable daily environmental changes in order to maintain internal and organismal homeostasis. Environmental stimuli (light, feeding, activity) capable of altering the phase of molecular rhythms are important tools employed by circadian biologists to increase understanding of the synchronization of circadian rhythms to the environment and to each other within multicellular systems. The central circadian clock, located in the suprachiasmatic nucleus (SCN) of the hypothalamus is largely responsive to light and is thought to entrain the phase of peripheral clocks via neurohumoral signals. Mice are nocturnal and consume most of their food during the dark cycle. Early studies demonstrated that altered metabolic cues in the form of time restricted feeding, specifically, feeding mice during the light cycle, resulted in an uncoupling of molecular clocks in peripheral tissues with those from the SCN. These studies showed as much as a 12-hour shift in gene expression in some peripheral tissues but not others. The shifts occurred without corresponding changes in the central clock in the brain. More recent studies have demonstrated that changes in cardiac physiology (heart rate, MAP) in response to time of food intake occur independent of the cardiac molecular clock. Understanding differences in physiology/function and gene expression in other organs both independently and in relation to the heart in response to altered feeding will be important in dissecting the roles of the various clocks throughout the body, as well as, understanding their links to cardiovascular pathology.